1999
DOI: 10.2166/wst.1999.0067
|View full text |Cite
|
Sign up to set email alerts
|

Interactive toxic effects of agrochemicals on aquatic organisms

Abstract: The effects of three common agrochemicals, lindane, methyl parathion and atrazine, on crustacean Daphnia magna, alga Selenastrum capricornutum and marine bacterium Vibrio fischeri were investigated in this study. Methyl parathion was the most toxic compound towards all three organisms, while lindane was more toxic to Daphnia magna and Vibrio fischeri than atrazine, and atrazine was more toxic to Selenastrum capricornutum than lindane. Among the three aquatic organisms, Selenastrum capricornutum was most sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 0 publications
0
32
0
2
Order By: Relevance
“…The model followed in this study was based on the theory of probability. If P 1 was the inhibition rate caused by a specific concentration of chemical A 1 and P 2 the inhibition rate caused by a certain concentration of chemical A 2 , Subsequently, the theoretically expected additive inhibition rate, when the concentrations of two chemicals are applied together, is shown by the following equation [34]:…”
Section: Interactive Toxicity Of Experimental Heavy Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The model followed in this study was based on the theory of probability. If P 1 was the inhibition rate caused by a specific concentration of chemical A 1 and P 2 the inhibition rate caused by a certain concentration of chemical A 2 , Subsequently, the theoretically expected additive inhibition rate, when the concentrations of two chemicals are applied together, is shown by the following equation [34]:…”
Section: Interactive Toxicity Of Experimental Heavy Metalsmentioning
confidence: 99%
“…The amount of metal was determined by inductively coupled plasma atomic emission spectroscopy (ICP-AES, Versamus, Australia). Based on the average weight of one Artemia neonate (which was determined to be 5µg) and Assuming the amount of metals in each solution measured by ICP-AES were absorbed by 1000 Artemia organisms, the quantity of metals absorbed by each animal and the bioconcentration factor (BCF) were determined subsequently [34,11].…”
Section: Copper and Cadmium Uptake At Different Individual And Mixed mentioning
confidence: 99%
“…In the natural environment there is a strong chance that mixtures contain both herbicides and insecticides, therefore it is important to investigate the impact of such combinations on plants. However, Kungolos, Samaras et al (1999) did evaluate two insecticides methyl parathion (organophosphorus) and lindane (organochlorine) and the herbicide atrazine on the growth of the algae Selenastrum capricornotum after 72 hours exposure. The EC50 was calculated for each compound and were 0.047, 0.69 and 0.145 mg/L for methyl parathion, lindane and atrazine respectively.…”
Section: Supporting Publications 2012:en-347 66mentioning
confidence: 99%
“…In the natural environment there is a strong chance that aquatic communities will also be exposed to mixtures of insecticides and herbicides. Two studies that looked at this were Kungolos et al (1999) and Cedergreen et al (2006) and they found little evidence of synergism and, at worst, they behaved additively. A similar trend of additivity was seen with studies that looked at herbicide combinations with the same mode of action.…”
mentioning
confidence: 99%
“…No-observed effect concentrations (NOECs), as the uppermost concentration being not significantly different from controls (P 0.05), were also calculated, using Origin 7.5 software. To test the interactive effect of both metals, the theoretically expected effect (E) of the binary mixtures on the test organisms was evaluated using the formula proposed by Kungolos et al (1999) and Hadjispyrou et al (2001). It was calculated using the following formula: E = P 1 + P 2 -P 1 P 2 /100, where E is the theoretical expected effect, P 1 is the inhibition caused by chemical A and P 2 is the inhibition caused by chemical B.…”
Section: > Statistical Analysismentioning
confidence: 99%